Kegiatan Penapisan Status Gizi Pada Kelompok Lanjut Usia Di Gereja ST. Fransiskus Asisi - Santoso, Alexander Halim; Waltoni, bobby Marshel Ancheloti; Jaya, I Made Satya Pramana; Satyanegara, William Gilbert; Wijaya, Dean Ascha; Destra, Edwin (Universitas 45 Surabaya, 2024)
Aging is associated with a gradual decline in physiological function, impacting multiple organ systems and reducing resistance to physical, cognitive, and mental stress. Adequate nutrition is critical for elderly people's health and quality of life. However, elderly people are susceptible to nutritional problems, including weight loss, decreased muscle mass (sarcopenia), and weakness. Decreased physical activity, hormonal changes, and metabolic adjustments influence these changes. The elderly population receiving treatment in institutions and hospitals has a significantly higher prevalence of malnutrition. This activity uses the Plan-Do-Check-Act (PDCA) framework to screen the nutritional status of the elderly using the Mini Nutritional Assessment (MNA) questionnaire. Activities were held at St. Fransiskus Assisi, Jakarta which included 35 participants. It was found that 10 people (27.78%) were at risk of experiencing malnutrition and 6 people (16.67%) experienced malnutrition. Early nutritional screening using the MNA questionnaire is essential to detect and prevent complications related to malnutrition in the elderly, thereby improving individual health outcomes and quality of life.